Цифрові технології моделювання соціальних процесів - Микитась, А. О. (ХНУРЕ, 2023)
This work deals with the digital modeling of social relations. Modeling is the main method of research in all fields of knowledge and a scientifically based method of evaluating the characteristics of complex systems, used to make decisions in various spheres of social activity. Existing and designed systems can be effectively investigated with the help of mathematical models (analytical, simulation), implemented on modem computers. The relevance of this topic, both in the conditions of a developed market economy and a transitional economy, is determined by the fact that modeling is an integral part of social forecasting, and the level of forecasting of social development processes determines the effectiveness of planning and management of social and other spheres.